Thiamine Therapy During Refractory Lactic Acidosis in Critically Ill Children - Fevzi Kahveci; İlker Fındık; Hasan Özen; Mert Kaan Coşkun; Hacer Uçmak; Anar Gurbanov; Burak Balaban; Merve Havan; Tanıl Kendirli (Galenos Yayinevi, 2024)
Introduction: Thiamin deficiency, which is an overlooked but important cause of lactic acidosis, can lead to several clinical symptoms, including neuropathy, cardiogenic shock, and death, even though it can be easily treated in critically ill children. Methods: A single-center, retrospective cohort study conducted between March 2020 and March 2022. Results: Twenty-two patients were included in the study. The mean age was 26.5 (range, 1-214) months. The median thiamin dose was 50 (range, 3-100) milligrams and the mean thiamin treatment duration was 4 (range, 1-16) days. The mean length of PICU when thiamin treatment was started was 8 (range, 2-177) days. Thiamin treatment was administered on the 2nd (1-5) day of lactic acidosis. The mean lactate values after thiamin treatment was 5.5 (range, 5-17) mmol/L at the 6th hour, 4.1 (range, 1.5-17) mmol/L at the 12th hour, 3.1 (1.4-20) mmol/L at the 24th hour, and 2.7 (range, 0.15-17) mmol/L at 48th hour. Eleven (50%) patients' lactate levels decreased below 4 mmol/L at the 12th hour of thiamin treatment. Blood gas values before thiamin treatment, lactate decrease trends, thiamin treatments' duration, and form, and patients' risk factors were not statistically significant in the two groups by 28-day mortality. Conclusion: We believe that in patients with lactic acidosis not directly related to a circulatory disorder, low clinical suspicion and early thiamin treatment of lactic acidosis is the right approach in the absence of specific diagnostic tests.